Validity and Reliability of a Mobile Device Application for Assessing Motor Performance in the 30-Second Sit-to-Stand Test - Eduardo Candido Veloso Ferreira; Amelia Pasqual Marques; Szymon Kulis; Jan Gajewski; Anderson Antunes da Costa Moraes; Manuela Brito Duarte; Gizele Cristina da Silva Almeida; Enzo Gabriel da Rocha Santos; Gustavo Henrique Lima Pinto; Andre Dos Santos Cabral; Givago da Silva Souza; Anselmo De Athayde Costa E Silva; et al. (IEEE Access)
This study aimed to test the validity and reliability of a mobile device application for capturing center of mass (CoM) acceleration signals in analyzing and describing events during the 30-second chair stand test. A sample of 25 healthy young adults was evaluated using a smartphone with an Android-based application positioned at the fifth lumbar vertebra level (L5). Performance data from the mobile device were compared to those captured by a three-camera motion capture system, which served as the gold-standard reference. Signal synchronization between the smartphone and the kinematic system was achieved using an initial vertical jump, during which the peak in vertical acceleration from both systems was used as a temporal alignment marker. The motor behavior of the CoM was subsequently observed during task execution. Data were processed offline using routines developed for MatLab software, focusing on the longitudinal axis and describing the event cycles. A total of 21 variables were extracted for analysis. Each movement cycle was divided into three phases: impulse (DP1), sit-to-stand (DP2), and stand-to-sit (DP3). This approach allowed for the observation of cycle duration, the number of cycles performed, execution frequency, positive and negative acceleration areas (AUC+ and AUC-) for each phase, maximum and minimum acceleration peaks (Max Acc and Min Acc) per phase, and the amplitude between these peaks. Mean values for each variable were tested for sample normality, followed by criterion validation and reliability analyses. The hypothesis was relatively validated against the gold standard for 18 out of 21 variables in the smartphone app. Only the for P2 duration and accelerations in AUC+P1 and AUC+P2 showed correlation values <0.70. Reliability was confirmed for 16 out of 21 variables; however, for DP1, DP2, and DP3 duration, as well as accelerations for Max Acc P2 and Min Acc P1, exhibited reliability values <0.70. Despite some limitations, the mobile application demonstrated partial effectiveness in observing CoM motor behavior during the proposed functional test.